History of scholarship : a selection of papers from the Seminar on the History of Scholarship held annually at the Warburg Institute - Ligota, C. R.; Quantin, Jean-Louis (Oxford-Warburg studies., 2006)
The history of scholarship has recently undergone a complete renewal: it is now a major branch of research. The contributors - all specialists of international standing - illustrate a variety of themes and approaches. A substantial introduction surveys the past vicissitudes of the history of scholarship and its current expansion. - ;The history of scholarship has undergone a complete renewal in recent years, and is now a major branch of research with vast territories to explore; a substantial introduction to History of Scholarship surveys the past vicissitudes of the history of scholarship and.